Training on making supplementary feeding (PMT) from cow's milk and moringa leaves - Tri Sunarsih; Pudji Astuti; Bangun P Nusantoro; Sarmin Sarmin; Endah Puji Astuti; Elvika Fit Ari Shanti; Alief Nur Insyiroh Abidah; Claude Mona Airin (Community Empowerment, 2024)
Chronic malnutrition leading to stunting remains a significant challenge in Indonesia. Supplemental feeding (PMT) based on cow's milk and moringa leaves holds potential to address this issue. This community service aimed to enhance community knowledge and skills in producing PMT from cow's milk and moringa leaves, which are rich in nutrients. The implementation methods included preparation, community socialization, theoretical and practical training, and follow-up monitoring and evaluation. The results of the community service showed a significant increase in participants' knowledge and skills regarding nutrition and PMT production. Participants were able to produce various PMT products such as yogurt, biscuits, sempol, and nuggets, and demonstrated creative ideas in developing new product variations.